2013
DOI: 10.1186/2213-0802-1-15
|View full text |Cite
|
Sign up to set email alerts
|

Role of WWOX and NF-κB in lung cancer progression

Abstract: It is generally agreed that the pro-inflammatory, pro-survival transcription factor NF-κB is a tumor promoter. Tumor necrosis factor alpha (TNF-α or TNF) mediates NF-κB activation. Tumor suppressor WWOX (FOR or WOX1) is a downstream effector of the TNF signaling. Thus, activation of both WWOX (FOR or WOX1) and NF-κB may occur during TNF signaling and/or under stress conditions. Indeed, the first WW domain of WWOX induces the activation of NF-κB-responsive promoter without TNF participation. It appears that WWO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 101 publications
(174 reference statements)
1
15
0
Order By: Relevance
“…After lung adenocarcinoma A549 cells were co-cultured with macrophages, NF-κB was activated in lung adenocarcinoma A549 cells and tumor cell proliferation and invasion abilities were significantly enhanced. The observed phenotype was consistent with previous research (26,27). The CaSR promoter region, which contains a functional response element κB, upregulates the NF-κB signaling pathway, activates CaSR, and participates in pathological processes, such as inflammatory bone resorption (28)(29)(30).…”
Section: Discussionsupporting
confidence: 92%
“…After lung adenocarcinoma A549 cells were co-cultured with macrophages, NF-κB was activated in lung adenocarcinoma A549 cells and tumor cell proliferation and invasion abilities were significantly enhanced. The observed phenotype was consistent with previous research (26,27). The CaSR promoter region, which contains a functional response element κB, upregulates the NF-κB signaling pathway, activates CaSR, and participates in pathological processes, such as inflammatory bone resorption (28)(29)(30).…”
Section: Discussionsupporting
confidence: 92%
“…Subsequent exposure of UV-treated cells to cold shock enhances accumulation of these proteins in the nucleus. NF-κB/p65 is a downstream effector of the TNF signaling, which blocks TNF-mediated cell death and thereby provides cancer survival [ 31 , 32 ]. Hyal-2 acts as an alternative receptor for TGF-β1 and a binding protein for WWOX [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that both WWOX and p53 function in a synergistic manner in causing apoptosis under various stress conditions. [8][9][10][11][12] Our supporting evidence revealed that NO, nitric oxide synthase 2 (NOS2), p53 and WWOX enhance in the bubbling death, whereas antiapoptotic TRAF2 blocks the cell death. 12 Importantly, nuclear accumulation of p53 and WWOX is needed to activate NOS2 to induce formation of NO.…”
Section: Wwox In Bubbling Deathmentioning
confidence: 93%
“…1,[8][9][10][11][12][13] In our most recent study, we have reported temperature-regulated ''bubbling death'' and its transition with apoptosis. 12 Bubbling death is defined as ''formation of a bubble from the nucleus and release of this swelling bubble to the cell surface that causes cell death''.…”
Section: Wwox In Bubbling Deathmentioning
confidence: 99%